P‐6: Reduction of Drain‐Current‐Drop Phenomenon in BCE a‐IGZO TFTs for 85‐in. 8K 120Hz GOA LCD. Issue 1 (28th June 2021) - Zheng, Ze-Ke; Li, Shan; Li, Yu-Zhi; Ge, Shi-Min; Gong, Cheng; Liu, Quan-Sheng; Son, Woosung; Xiao, Jun-Cheng; Zhao, Bin
Abstract : In order to avoid the drain current drop (DCD) issue in GOA circuits of Cu‐process BCE a‐IGZO 85inch 8K 120Hz LCD Displays, which causes the decrease of TFT electrical characteristics and poor transmission of gate signal, leading to the failure of GOA function, the mechanism and reduction of DCD effect through process optimization was studied in this paper.